Utilization of Edge Information in Handwritten Numerals Recognition - Kamal , Nada Najeel (Iraqi Journal of Science, 2022)
The recognition of handwritten numerals has many applications in automatic identification and cognition. This research contains three experimented scenarios to recognize the handwritten English (i.e. Arabic) numerals. In the first scenario the bilinear interpolation of the image is used, while in the second scenario and after the bilinear interpolation is being applied, the Sobel operators are applied on the resulted interpolated image. In the third scenario which represents the last one, the effect of normalization of image dimensions is tested. 550 images of handwritten numerals were tested. Three types of tests were conducted for each scenario namely: trained-set test, not-trained-set test and comprehensive-set test. Depending on the results obtained from the comprehensive-set test, the best scenario is the second scenario of bilinear interpolation followed by Sobel operators which leads to excellent success rate reaches to 97.63%.